Seasonal nitrogen uptake strategies in a temperate desert ecosystem depends on N form and plant species. (8th January 2020) - Zhuang, W.; Li, J.; Yu, F.; Dong, Z.; Guo, H.
Abstract: Symbiotic plants might be able to regulate a limited nitrogen (N) pool, thus avoiding and reducing competition for resources, through the uptake of different chemical N forms. Our aim was to see whether coexisting herbs showed preference for different forms of N in a temperate desert. We conducted a situ experiment using the 15 N labeling method in the Gurbantunggut Desert of Northwestern China dominated by Erodium oxyrrhynchum, Hyalea pulchella, Nonea caspica and Lactuca undulata during their growing period (April and May). Four desert herb species preferentially relied on 15 N‐NO3 for their N nutrition. Multi‐factor analysis of variance (ANOVA) analysis results showed that species, N forms, months, and soil depths strongly affected N uptake rate. The uptake rate by herbs was higher in May than in April, and higher at 0–5 cm than at 5–15 cm soil layers. Erodium oxyrrhynchum, N. caspica and L. undulata showed different preference on N form over months. Erodium oxyrrhynchum and L. undulata changed their uptake preference from more 15 N‐Glycine in April to more 15 N‐NH4 in May. Although the N uptake rate of four desert herbs varied across different soil depths and months, all species absorbed more inorganic N compared with organic N. The higher preference for 15 N‐NO3 and 15 N‐NH4 over 15 N‐Gly possibly reflects adaptation to different N forms in temperate desert. Abstract : We aim to investigate whether different plant species co‐existing in the Gurbantunggut Desert differ in their N acquisition strategies over the growing season. The results showed that the distinct N acquisition strategies used by four desert herbs varied across different months and soil depths. These findings are more helpful in further understanding the plasticity of nutrient utilization issues of different plant species in response to N‐limited conditions of desert ecosystems.